Physiological Quality of Bean Seeds Cultivated with Rhizobia Reinoculation and Azospirillum Co-Inoculation at Different Growth Stages - Nathan Mickael de Bessa Cunha; Itamar Rosa Teixeira; Gisele Carneiro da Silva Teixeira; Ednaldo Cândido Rocha; Tamires Ester Peixoto Bravo; Andressa Laís Caldeira de Souza; Eulina Fernandes Damião; Alexandre Marcos Sbroggio Filho (Microorganisms)
This study evaluates the impact of Rhizobium tropici reinoculation and Azospirillum brasilense co-inoculation at different growth stages on the physiological quality of common bean seeds. A randomized block design was used, assessing germination, vigor, electrical conductivity, seedling length, and dry mass. Treatments T7 (co-inoculation R. tropici + A. brasilense at R5) showed the highest germination rates, indicating enhanced seed viability. The accelerated aging test revealed that T7 exhibited greater resistance to stress, presenting greater seedling vigor, whereas T10 and T11 were more susceptible. The electrical conductivity results remained stable across treatments, suggesting that cell membrane integrity was not significantly compromised. Seedling length and dry mass did not present significant variations, reinforcing the idea that early germination and vigor are primary indicators of seed quality. Canonical discriminant analysis and MANOVA confirmed significant treatment differences, highlighting the influence of inoculation strategies on seed physiology. Overall, co-inoculation with Rhizobium tropici and Azospirillum brasilense (particularly in T7) demonstrated potential to improve seed quality at lower cost, offering sustainable alternatives for optimizing agricultural production.